2022
DOI: 10.3389/fendo.2022.981487
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of osteoporosis in obesity and type 2 diabetes in aging women and men: The mechanisms and roles of increased bone marrow adiposity

Abstract: Osteoporosis is defined as a systemic skeletal disease characterized by decreased bone mass and micro-architectural deterioration leading to increased fracture risk. Osteoporosis incidence increases with age in both post-menopausal women and aging men. Among other important contributing factors to bone fragility observed in osteoporosis, that also affect the elderly population, are metabolic disturbances observed in obesity and Type 2 Diabetes (T2D). These metabolic complications are associated with impaired b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 217 publications
0
38
0
Order By: Relevance
“…Te past half-century has witnessed the development of scanning modalities for BMD and bone microarchitecture measurements, such as dual-energy X-ray absorptiometry or quantitative CT [5]. Te gradual imbalance between bone formation and resorption can be caused by multiple factors, including aging, estrogen defciency, and prolonged immobilization, followed by disruption of normal apoptosis and autophagy with excessive infammation [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te past half-century has witnessed the development of scanning modalities for BMD and bone microarchitecture measurements, such as dual-energy X-ray absorptiometry or quantitative CT [5]. Te gradual imbalance between bone formation and resorption can be caused by multiple factors, including aging, estrogen defciency, and prolonged immobilization, followed by disruption of normal apoptosis and autophagy with excessive infammation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The past half-century has witnessed the development of scanning modalities for BMD and bone microarchitecture measurements, such as dual-energy X-ray absorptiometry or quantitative CT [ 5 ]. The gradual imbalance between bone formation and resorption can be caused by multiple factors, including aging, estrogen deficiency, and prolonged immobilization, followed by disruption of normal apoptosis and autophagy with excessive inflammation [ 6 ]. Preventing the occurrence and minimizing the risk of fractures are the main goals of several pharmacological agents for osteoporosis management either by inducing bone formation or by reducing bone resorption, including zoledronic acid, calcitonin, and salmon calcitonin [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They may thus exhibit various degrees of bone fragility, that progressively impact bone cellular processes as well as various body systems, as well as contributing to alterations in local bone homeostasis and systemic metabolism 7 and metabolic disorders, 12 especially if undetected. 13 Hsu et al, 14 found that the risks of an individual acquiring osteoporosis, osteopenia, or nonspine fractures was significantly higher for subjects with a higher percentage of body fat independent of body weight, physical activity, and age. As such it appeared that having a high fat mass could impose a negative effect on bone mass that is different from that of normal weight-bearing.…”
Section: Resultsmentioning
confidence: 99%
“…Once identified, observational studies began to report that BMAT is often inversely associated with bone mineral density (BMD). For example, this relationship has consistently been demonstrated during aging (Shen et al, 2014), post-menopausal osteoporosis (Shen et al, 2014), anorexia nervosa (Bredella et al, 2009), as well as during obesity (Elia, 2012;Rinonapoli et al, 2021;Ali et al, 2022). In these scenarios, patients often present with an increase in BMAT along with a decrease in bone mass or BMD (93).…”
Section: Adipose Tissuementioning
confidence: 97%
“…However, it is accepted within the field that systemic inflammation and/or glucose intolerance associated with obesity results in bone fragility and increased fracture occurrence (Turcotte et al, 2021). Aging, menopause, obesity with or without diabetes all of which has been shown to be associated with bone loss or bone fragility have been shown to cause bone marrow adipose tissue expansion (Ali et al, 2022). Noteworthy, recent work has demonstrated that in addition to estrogen, FSH also has profound impact on adipose tissue.…”
Section: Adipose Tissuementioning
confidence: 99%